2016
DOI: 10.1186/s12885-016-2889-6
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of human epidermal growth factor receptor family protein expression in operable pancreatic cancer

Abstract: BackgroundPrognostic factors aid in the stratification and treatment of cancer. This study evaluated the prognostic significance of human epidermal growth factor receptor (HER) family members (HER1–4) expression in patients with operable pancreatic cancer.MethodsThe expression of individual HER proteins in patient tissue specimens was detected by immunohistochemistry staining. Patient follow-up time was between 1.0 and 78.1 months.ResultsPositive expression of HER1, HER2, HER3 and HER4 was detected in 41.4, 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…In some clinical samples, EGFR showed a significantly higher expression in pancreatic adenocarcinoma compared with normal pancreatic tissue and were confirmed by TASC scoring as a promising imaging target. In pancreatic adenocarcinoma, EGFR expression varies from 25% to 69% in different studies and has been associated with advanced stage, metastastic disease, poor differentiation, and survival . EGFR signalling is also one of the main reasons behind the early invasion and metastasis of pancreatic cancer, which leads to the poor prognosis of this disease …”
Section: Discussionmentioning
confidence: 99%
“…In some clinical samples, EGFR showed a significantly higher expression in pancreatic adenocarcinoma compared with normal pancreatic tissue and were confirmed by TASC scoring as a promising imaging target. In pancreatic adenocarcinoma, EGFR expression varies from 25% to 69% in different studies and has been associated with advanced stage, metastastic disease, poor differentiation, and survival . EGFR signalling is also one of the main reasons behind the early invasion and metastasis of pancreatic cancer, which leads to the poor prognosis of this disease …”
Section: Discussionmentioning
confidence: 99%
“…This leads to an auto and/or trans-phosphorylation of C-terminal region of the intracellular tyrosine kinase domain leading to the activation of various downstream signaling pathways such as PI3K-AKT, RAS/RAF/MAPK, JAK-STAT and PLC-γ1 that regulates proliferation, metabolism, angiogenesis, cell progression and survival (7)(8)(9). In some studies, aberrant expression and activation of HER-mediated signaling has been associated with tumor aggressiveness and a poorer prognosis in patients with pancreatic cancer (7,(10)(11)(12)(13). However, of the HER inhibitors, only the reversible EGFR-specific erlotinib has been approved by the US FDA for the treatment of locally advanced, unresectable or metastatic pancreatic cancer when used in combination with gemcitabine (14).…”
Section: Introductionmentioning
confidence: 99%
“…Poteet et al have investigated a combination of EGFR inhibitors (cetuximab, gefitinib) with trametinib (MEK-inhibitor) and concluded that this combination could present a novel effective treatment for PDAC (16). Moreover, the authors found possible predictors of sensitivity to EGFR-inhibitors (mesothelin and TGF-α) (17).…”
Section: Egfr-inhibitorsmentioning
confidence: 99%